A unified 3‐D ADI‐FDTD algorithm with one‐step leapfrog approach for modeling frequency‐dependent dispersive media. (24th July 2019) - Xie, Guoda; Huang, Zhixiang; Fang, Ming; Wu, Xianliang
Abstract: A unified 3‐D alternating‐direction‐implicit finite‐difference time‐domain algorithm with one‐step leapfrog approach is provided for analyzing the frequency‐dependent dispersive media. The dielectric parameter in the frequency domain is described by the modified Lorentz model. Simultaneously, an order reduction scheme is utilized to synchronize the auxiliary differential equations (ADE) technique with the main algorithm. The numerical cases are performed, and the results indicate that the proposed method possesses higher efficiency under allowable accuracy when compared with the analytical method and other time domain numerical schemes.